Expectations and changing attitudes of bar workers before and after the implementation of smoke-free legislation in Scotland - MacCalman Laura; Miller Brian G; Semple Sean; Hilton Shona; Petticrew Mark; Dempsey Scott; Naji Audrey; Ayres Jon G (BMC, 2007)
Abstract Background In Scotland on March 26, 2006 a comprehensive prohibition on smoking in all enclosed public places was introduced. This study examines bar workers' attitudes towards a smoke-free working environment. Methods An intervention study comparing bar workers' opinions before and after the implementation of the smoke-free legislation. Bars were randomly selected in three Scottish cities (Glasgow, Edinburgh & Aberdeen) and towns (Aberdeenshire & Borders). Bar workers were recruited from 72 bars that agreed to participate from159 approached. Pre- and post-implementation attitudes towards legislation, second-hand smoke and smoke-free working environments were compared. Results Initially the majority of bar workers agreed with the proposed legislation on smoking (69%) and the need for it to protect the health of workers (80%), although almost half (49%) thought the legislation would damage business. In 266 bar workers seen at both surveys, a significant positive attitudinal change towards the legislation was seen. Post-implementation, support for the legislation rose to 79%, bar workers continued to believe it was needed to protect health (81%) and concerns about the impact on business were expressed by fewer than 20%. Only the statement that the legislation would encourage smokers to quit showed reduced support, from 70% pre-implementation to fewer than 60% post-implementation. Initial acceptance was greater among younger bar workers; older workers, initially more sceptical, became less so with experience of the legislation's effects. Conclusion This study shows that bar workers had generally positive attitudes towards the legislation prior to implementation, which became stronger after implementation. The affirmative attitudes of these key stakeholders are likely to contribute towards the creation of 'smoke-free' as the new social norm.